Effect of intravenous vitamin C administration on chemotherapy-induced adverse events in patients with nasopharyngeal cancer - Peesit Leelasawatsuk; Pasawat Supanimitjaroenporn; Nattida Rodsom; Theepat Wongkittithaworn; Manupol Tangthongkum (PLoS ONE, 2026)
Nasopharyngeal carcinoma is prevalent in Thailand, with a substantial proportion of cases diagnosed at advanced stages. The standard treatment, concurrent chemoradiotherapy, is associated with considerable adverse effects, which may compromise therapeutic efficacy and diminish patients’ quality of life. While vitamin C has shown potential in reducing chemotherapy-induced toxicities in some cancers, its effects in nasopharyngeal carcinoma remain unclear. In this randomized, double-blind, placebo-controlled trial, patients with nasopharyngeal carcinoma undergoing concurrent chemoradiotherapy were assigned to receive either 2 g of intravenous vitamin C or placebo prior to chemotherapy. The incidence of gastrointestinal adverse effects—including nausea, anorexia, mucositis, diarrhea, and dysphagia—did not differ significantly between groups. However, longitudinal analysis demonstrated a significantly attenuated decline in platelet counts in the vitamin C group compared with placebo. Although intravenous vitamin C did not reduce gastrointestinal toxicities, the observed platelet preservation suggests a potential supportive effect that warrants further investigation. Trial registration The study was registered with the Thai Clinical Trial Registry (TCTR20190316003) on March 16, 2019.